PERANCANGAN SISTEM INFORMASI PEMESANAN GAS LPJ BERBASIS ONLINE PADA PANGKALAN TETI TANJUNG MUTIARA KAB. AGAM - Arman Arman; Elizamiharti Elizamiharti; Nelfira Nelfira; Fauziah Yovi Yanti (Universitas Lancang Kuning, 2021)
This research is motivated by the high interest and demand for LPG gas among the people in Tanjung Muatiara resulting in LPG gas often experiencing scarcity at several gas bases, all because the people only make reservations at bases in their home environment. To get information about LPG gas supplies, the public must visit bases to directly inquire of LPG gas supplies to the base owner. For this reason, through this research a website-based online design and application of LPG gas ordering information system was conducted. The system design in this application program uses the PHP programming language and MySQL database. The software development model used in this study is the waterfall SDLC model often also called sequential linear nods or classic life cycles. This study aims to build an information system that can provide information about LPG gas inventories at Teti Tanjung Mutiara Base and implement a website as a medium to promote and place online orders at Teti Tanjung Mutiara so as to facilitate the ordering process by customers.